2020
DOI: 10.20377/jfr-422
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Special Issue “Parental work and family/child well-being”

Abstract: The "new economy" is characterized by increasing levels of nonstandard employment. A significant proportion of employees work very long hours, work with high intensity, or have long commutes to work. Also, many workers struggle to secure adequate, stable employment or good quality jobs, and work evening and night shifts or work multiple jobs in order to make ends meet. This special issue examines the consequences of the new economy for the wellbeing of family and children. The studies included in this special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This translated into a higher incidence of precariousness and inequalities: today, being in paid work does no longer protect from poverty (Bonoli, 2007;Marx & Nolan, 2014). The polarisation between well-paid, stable jobs on the one hand, and lowpaid, non-standard, non-permanent jobs on the other (Palier & Thelen, 2010) have consequences for individuals (different levels of social protection, access to health insurance, career perspectives) (Emmenegger et al, 2012), for child rearing and children's well-being (Pollmann-Schult & Li, 2020;Siippainen et al, 2023) and for society at large (unemployment rates, poverty and inwork poverty, rising inequality) (Marx & Nolan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This translated into a higher incidence of precariousness and inequalities: today, being in paid work does no longer protect from poverty (Bonoli, 2007;Marx & Nolan, 2014). The polarisation between well-paid, stable jobs on the one hand, and lowpaid, non-standard, non-permanent jobs on the other (Palier & Thelen, 2010) have consequences for individuals (different levels of social protection, access to health insurance, career perspectives) (Emmenegger et al, 2012), for child rearing and children's well-being (Pollmann-Schult & Li, 2020;Siippainen et al, 2023) and for society at large (unemployment rates, poverty and inwork poverty, rising inequality) (Marx & Nolan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Work–family conflict has been a traditional way of interpreting work–family reconciliation. Research on non‐standard work schedules and their effects on families has centred on questions of parental processes, such as the division of labour between parents or parent–child relationships, and parental and child well‐being, including health and socio‐emotional well‐being (Pollmann‐Schult & Li, 2020). Many studies have shown that non‐standard working times have negative consequences for the couple's relationship, the couple's work–family reconciliation or child development.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that non‐standard working times have negative consequences for the couple's relationship, the couple's work–family reconciliation or child development. Other studies, however, have also demonstrated beneficial aspects of working non‐standard hours, such as the above‐mentioned more equal division of unpaid work between parents (for an overview, see e.g., Pollmann‐Schult & Li, 2020 or Grzyvacz, 2016). According to Pollmann‐Schult and Li et al (2020), family strategies can play an important role in understanding the either negative or positive impacts of parental non‐standard work schedules on family well‐being.…”
Section: Introductionmentioning
confidence: 99%